Linking Faith and Conservation in Sacred and Community Forests of Far Western Nepal - Alexander M. Greene; Rajendra Bam; Krishna S. Thagunna; Jagdish Bhatta; Renuka Poudel; Laxmi D. Bhatta; Rajindra K. Puri (Religions)
Faith and conservation are deeply entangled in the Himalayas. Focusing on a single Hindu community in Darchula, Nepal, we investigate the forms of governance used to manage an extensive sacred forest on a nearby mountain and five smaller community forests at its base. To understand the effects of these different models of governance, we use a mixed method approach to examine two indicators of biocultural diversity: forest resource use and spiritual practices. These data reveal a concentrated human impact on the community forests through the harvesting of plant resources, while the sacred forest receives a far smaller impact from these activities. The community considers the sacred forest and mountain to be the home of a local god, who is worshiped in annual pilgrimages attended by people throughout the region. Spiritual practices in the community forests are more localized, small-scale, and associated with women’s traditions. From a biodiversity perspective, the sacred forest appears useful for conservation because of its large size and the spiritual governance that protects it from most human impacts. In terms of biocultural diversity, however, the two forest types play complementary roles in supporting biocultural heritage: the community forests provide the resources required for daily life, while the sacred forest nourishes identity, embodies communal history, and upholds the fertility of the land. The two forest types ultimately blend together in the ways that they are valued and used by people, showing that only a landscape-level perspective can provide a full understanding of the links between forest and community.